Efektifitas Game Edukasi sebagai Media Pembelajaran Kebudayaan Permainan Tradisional Siswa Sekolah Dasar di Indonesia - Noorlela Marcheta; Richard Abdul Kareem (Journal on Education, 2023)
Indonesia is a country that has cultural diversity. However, currently, the awareness and knowledge of the younger generation about the traditional culture of the Indonesian nation are increasingly extinct due to globalization which has caused the entry of foreign cultures that affect the younger generation and oblivious their role in preserving the nation's culture. Currently, elementary school students have been givens lessons related to cultural introduction. Based on the results of the interviews, the teachers experienced difficulties in practicing cultural material. Because to be able to practice traditional games require tools and a field for practicing. The next problem is the delivery of material in a traditionals way by teachers which causes the learning atmosphere to be less pleasant and a boring. So it requires interactive learning media that aims to increase student interest so the students can understand the material better. This research aims to increase the effectiveness of education on the introduction of traditional game culture in Indonesia based on 2D games. This game is a mobile-based learning media for elementary school students as a tool to help teachers and students introduce traditional games.